Evaluation of the influence of additives in water-based drilling fluid with applicability to shales calumbi formation - Felisardo, Raul José Alves; Silva, Gabriela Menezes; Lourenço, Everton dos Santos; Miranda, Cláudia Santana Arcieri; Figueredo Filho, Josan Carvalho de; Serpa, Fabiane Santos (Brazilian Journal of Production Engineering, 2022)
Fluids are essential in the drilling stage of oil well. The composition changes according to application. To improve the efficiency, the industry investigates different additives for drilling muds with applicability in reactive formations such as the Calumbi Formation. Thus, this work proposes a formulation of an aqueous based drilling fluid with the objective of evaluate the reactivity in shales of the Calumbi Formation. The addition of the addition of inhibitors additives was evaluated (potassium chloride and cationic polymer) and viscosifiers (xanthan gum and carboxymethylcellulose) was evaluated. Rheological properties and fluid wettability measurements were performed according to specific standards. The results showed that the simultaneous use of potassium chloride and cationic polymer showed low reactivity in the Calumbi Formation shales. The presence of the xanthan gum promoted a smaller interaction between fluid and rock. The proposed formulation has characteristics compatible with a formation, that has great relevance to the Sergipe-Alagoas Basin.
Keywords: Drilling fluids; inhibitors; reactive formations; rheology